Pulmonary Embolism Originating from a Hepatic Hydatid Cyst Ruptured into the Inferior Vena Cava: CT and MRI Findings - Necdet Poyraz; Soner Demirbaş; Celalettin Korkmaz; Kürşat Uzun (Case Reports in Radiology)
Pulmonary embolism due to hydatid cysts is a very rare clinical entity. Hydatid pulmonary embolism can be distinguished from other causes of pulmonary embolism with contrast-enhanced computed tomography (CECT) and magnetic resonance imaging (MRI). MRI especially displays the cystic nature of lesions better than CECT. Here we report a 45-year-old male patient with the pulmonary embolism due to ruptured hydatid liver cyst into the inferior vena cava.